The Snail Darter and the Dam - Zygmunt J. B. Plater (Yale University Press, 2013)
This book grew out of a tumultuous half- dozen years when a group of my students and I at the University of Tennessee took up the cause of embattled local farmers and a river threatened by a very dubious federal dam project. Fighting to save the river and its remarkable valley, we used the federal Endangered Species Act and the snail darter, a little fi sh threatened with extinction, as our only available legal leverage. The Snail Darter and the Dam is a true- life parable, revealing major twists, turns, opportunities, and hazards, as a citizen- based public interest campaign wrestles its way through scientifi c, economic, po liti cal, and legal obstacles in a stubborn attempt to straighten out an enduring offi cial mistake. Was the battle between the Tellico Dam, being built by the federal Tennessee Valley Authority (TVA), and the little snail darter the â€œmost extreme environmental case ever,â€ as pundits and politicians have said? Critics have long denigrated the tiny endangered fi sh and the â€œfringe lunaticsâ€ (to quote Fox News personality Sean Hannity) who persuaded the U.S. Supreme Court to halt a â€œhuge Tennessee Valley hydroelectric damâ€ that would destroy the little fi shâ€™s last known natural population. The clash happened more than thirty years ago, but Hannity and other conservatives, like Rush Limbaugh, Ann Coulter, George Will, Roger Ailes, Justice Antonin Scalia, and their cohort in Congress, still invoke the snail darter as a sarcastic put- down, using it to characterize progressive initiatives as liberal extremism. The little fi sh has also entered public rhetoric more broadly. A national controversy over the snail darter fi lled newspapers, talk shows, and tele vi sion news coverage. It was one of the three biggest environmental press stories of its de cade, understood then and now, even by liberals, as an example of governmental protectionism that went too far.